Alternating Current Electroluminescence for Human-Interactive Sensing Displays - Jiang, Wei; Lee, Seokyeong; Zan, Guangtao; Zhao, Kaiying; Park, Cheolmin (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2024)
The development of stimuli-interactive displays based on alternating current (AC)-driven electroluminescence (EL) is of great interest, owing to their simple device architectures suitable for wearable applications requiring resilient mechanical flexibility and stretchability. AC-EL displays can serve as emerging platforms for various human-interactive sensing displays (HISDs) where human information is electrically detected and directly visualized using EL, promoting the development of the interaction of human-machine technologies. This review provides a holistic overview of the latest developments in AC-EL displays with an emphasis on their applications for HISDs. AC-EL displays based on exciton recombination or impact excitations of hot electrons are classified into four representative groups depending upon their device architecture: 1) displays without insulating layers, 2) displays with single insulating layers, 3) displays with double insulating layers, and 4) displays with EL materials embedded in an insulating matrix. State-of-the-art AC HISDs are discussed. Furthermore, emerging stimuli-interactive AC-EL displays are described, followed by a discussion of scientific and engineering challenges and perspectives for future stimuli-interactive AC-EL displays serving as photo-electronic human-machine interfaces. This review summarizes the development of stimuli-interactive displays based on alternating current (AC) driven electroluminescence (EL), where human information is electrically detected and visualized. The review categorizes AC-EL displays by device architectures, discussing state-of-the-art applications, emerging advancements, challenges, and perspectives for future photo-electronic human-machine interfaces.image